Medical Management of Incomplete Abortion Using Pervaginal Misoprostol in Chittagong Medical College Hospital - Mamataz, Zakia; Hosain, Suman Nazmul; Bhattacharjee, Sulekha; Aktar , Jahanara; Akhtar, Rowshan (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: A miscarriage is a pregnancy that ends before the baby can survive outside the womb because it has not yet reached viability. A miscarriage may be early - during the first 14 weeks of pregnancy, or late. Objective of the study was to see the outcome of pervaginal misoprostol in the medical management of incomplete abortion. Methods: This cross-sectional study was performed between July and December 2015 on patients with incomplete abortion, who wanted to undergo medical management at the Department of Gynecology and Obstetrics, Chittagong Medical College Hospital. 100 consecutive incomplete abortion cases, who fulfilled the inclusion and exclusion criteria were enrolled for the study. Information about management with per vaginal misoprostol, possible side effects and success rate was given to the women. 600 microgram misoprostol was given per vaginally. Interval between administration of misoprostol and expulsion of product of conception was recorded. Result: The mean age was found 25.0±6.4 years and the mean gestational age was found 10.2±2.0 weeks. The mean duration of bleeding was found 8.6±10.9 days. No side effect was found in 86 (86%), nausea in 7(7%), vomiting in 5 (5%) and cramping in 2 (2%) patients. For majority (76%) of the patients, single dose of Misoprostol was enough to achieve the goal. However, 24 patients didn’t respond and received a second dose. The mean induction expulsion interval was 10.83±5.45 hours. Retained product of conception was found in 14 patients. Medical management failed in these 14 patients and ultimately Dilatation & Curettage (D & C) was done. Conclusion: Pervaginal Misoprostol is as effective as method of treating incomplete abortion at uterine size of <12 weeks. Treatment with misoprostol can reduce the demand for surgical evacuation in cases of incomplete abortion. The acceptability of misoprostol appears higher. Pervaginal Misoprostol appears suitable for the treatment of incomplete abortion in the developing countries. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 42-48